Pelletizing process by adding titanium-containing composite binder into fine-fraction titanium concentrate

Through the sphere making process of fine-grain titanium concentrate with titanium-containing composite binder, the problems of difficulty in feeding and lowering of titanium dioxide in electric furnace smelting are solved, and efficient and green titanium resource recycling and utilization are achieved.

CN119710223APending Publication Date: 2025-03-28PANZHIHUA UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411912310.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Fine-grained titanium concentrates are difficult to add due to excessive fine particle size in electric furnace smelting, and the utilization rate is low. In the existing binders, oxides such as calcium, magnesium, silicon, and aluminum, enter the titanium slag to reduce the titanium dioxide grade, which is costly and poor thermal stability.

Method used

The sphere making process of fine-grain titanium concentrate plus titanium-containing composite adhesive is used to prepare titanium concentrate oxidized pellets through rolling sphere making, drying and oxidation and roasting processes, and the good bonding performance and high titanium dioxide grade of the titanium-containing composite adhesive are used.

Benefits of technology

The spherical properties and high temperature strength of fine-grained titanium concentrate are improved, production costs are reduced, impurities in titanium slag are avoided, and efficient and green recycling of titanium resources are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710223A_ABST
    Figure CN119710223A_ABST
Patent Text Reader

Abstract

The invention discloses a pelletizing process by adding a titanium-containing composite binder into fine-fraction titanium concentrate, and belongs to the field of metallurgy. The process specifically comprises the following steps: uniformly mixing fine-grained titanium concentrate with a titanium-containing composite binder according to a mass ratio of 100: (5-20) to obtain a mixed material, and then carrying out rolling pelletizing, drying and oxidizing roasting to obtain the titanium concentrate oxidized pellets. The particle size of the fine-fraction titanium concentrate is smaller than 75 microns, and the grade of titanium dioxide is 40-52%; the particle size of the composite binder is smaller than 38 microns, and the grade of titanium dioxide is not lower than that of fine-fraction titanium concentrate. The process is low in raw material cost, and the utilization rate of the fine-fraction titanium concentrate is high; the adopted titanium-containing binder has the outstanding advantage that the grade of titanium dioxide in the prepared titanium concentrate oxidized pellets is not reduced; the prepared titanium concentrate oxidized pellets have relatively high pellet high-temperature strength and relatively good high-temperature thermal stability; according to the technical scheme, the technical problems existing in an existing fine-grain titanium concentrate pelletizing process can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metallurgy, and in particular relates to a ball-making process of fine-grained titanium concentrate with a titanium-containing composite binder. Background Art

[0002] Fine-grained titanium concentrate (referring to titanium concentrate with a particle size of less than 75μm, especially titanium concentrate with a particle size of less than 37μm) is the main new product for deep titanium selection from vanadium-titanium magnetite in recent years. However, due to its fine particle size, when used as a raw material for titanium slag smelting, it has problems such as difficulty in entering the furnace, poor permeability of the material layer, low reduction efficiency, high power consumption, reduced titanium resource recovery rate and difficulty in dust removal treatment of electric furnace exhaust. Therefore, it has not been effectively utilized yet.

[0003] At present, the production of titanium slag in China mostly adopts semi-closed electric (arc) furnaces. A large amount of dust ash (titanium slag ash) will be collected during the treatment of the tail gas of the electric furnace. Every ton of titanium slag produces about 85-100 kg of titanium slag ash, which contains a large amount of iron oxide and titanium oxide, with a TiO2 content of 20-50% and a FeO+Fe2O3 content of 20-40%. Due to the low TiO2 grade and fine particle size of titanium slag ash, it has not been effectively utilized, resulting in a waste of resources.

[0004] Titanium concentrate pellets are mainly used as raw materials for electric furnace smelting of titanium slag. According to different preparation methods, they can be divided into oxidized pellets, cold-set pellets, metallized pellets, etc. However, the molding of various pellets is inseparable from binders. Existing binders are mainly divided into: inorganic binders with siliceous components such as bentonite, diatomaceous earth, and saponite, organic binders with dextrin, asphalt, PVA, CMC, syrup, starch, etc., and organic-inorganic composite binders. These binders have the following problems: (1) The main components of the existing inorganic binders contain oxides such as calcium, magnesium, silicon, and aluminum. After the titanium concentrate pellets are smelted, the oxides such as calcium, magnesium, silicon, and aluminum enter the titanium slag, reducing the titanium dioxide grade of the titanium slag; (2) Organic-inorganic composite binders are not only expensive, the production cost of the pellets is high, but also have poor thermal stability and are easily decomposed at high temperatures, resulting in poor high-temperature strength of the pellets or even pulverization.

[0005] CN117845048A discloses an ultrafine iron ore concentrate pellet and a preparation method thereof, wherein the composite binder used is a combination of bentonite and an organic binder, and the obtained iron ore concentrate pellet has a general thermal stability. CN101921911A discloses a pellet binder and a preparation method thereof, wherein the binder is composed of iron-containing tailings, bentonite and an activator, and the binder is used to make full use of the Fe element in the iron-containing tailings, but the addition of bentonite will increase the content of oxide impurities such as Ca and Mg, which will have an adverse effect on the subsequent utilization of the Fe element, and the addition of an activator will increase the cost of the binder. CN113215396A discloses a method for granulating fine-grained titanium concentrate or titanium-rich material, wherein fine-grained titanium concentrate or titanium-rich material, graphite powder and pulp waste liquid are used for granulation, wherein the cost of the added graphite powder is relatively high, and the thermal stability of the pellets granulated using pulp waste liquid is relatively low. Summary of the invention

[0006] The technical problems to be solved by the present invention are:

[0007] (1) Fine-grained titanium concentrate is too fine, which makes it difficult to add materials during electric furnace smelting. It is very easy to be carried out of the furnace by the furnace gas (tail gas), resulting in reduced utilization. At the same time, due to the small particle size, the permeability of the material layer in the furnace will deteriorate, the heat transfer efficiency will decrease, the reduction efficiency will decrease, the power consumption will increase, and foamy slag will be easily formed, resulting in poor slag-iron separation effect, unsmooth smelting process, and increased production costs.

[0008] (2) During the smelting process, the existing fine-grained titanium concentrate pelletizing (granulation) binders use inorganic and organic-inorganic composite binders, and oxides such as calcium, magnesium, silicon, and aluminum easily enter the titanium slag as impurities, resulting in a decrease in the titanium dioxide grade of the titanium slag.

[0009] (3) The existing organic binders and organic-inorganic composite binders used for pelletizing (granulating) fine-grained titanium concentrate are relatively expensive and have poor thermal stability, resulting in a high production cost for titanium concentrate pellets.

[0010] The technical solution adopted by the present invention to solve the above technical problems is: a ball-forming process of fine-grained titanium concentrate with a titanium-containing composite binder, wherein the fine-grained titanium concentrate and the titanium-containing composite binder are mixed at a mass ratio of 100:(5-20) to obtain a mixed material, and then the mixture is subjected to the steps of rolling ball-forming, drying, and oxidation roasting to obtain titanium concentrate oxidized pellets.

[0011] The particle size of the fine-grained titanium concentrate is less than 75 μm, and the titanium dioxide grade is 40-52%.

[0012] The particle size of the titanium-containing composite binder is less than 38 μm, and the grade of titanium dioxide is not lower than that of fine-grained titanium concentrate.

[0013] The titanium-containing composite binder is a mixture of at least one of titanium dioxide, titanium ash powder and titanium yellow powder and titanium slag ash in any proportion.

[0014] Furthermore, the content of titanium dioxide in the titanium slag ash is 20-50%.

[0015] Furthermore, the content of titanium dioxide in the titanium dioxide is ≥98%.

[0016] Furthermore, the content of titanium dioxide in the titanium ash powder is ≥89%.

[0017] Furthermore, the content of titanium dioxide in the titanium yellow powder is ≥95%.

[0018] The rolling ball making process is as follows: adding 10-30% of water by weight to the mixed material, rolling the mixed material into balls in a disc ball making machine at a rotation speed of 60-70 rpm to obtain wet pellets.

[0019] Furthermore, the particle size of the wet pellets is 3-8 mm, the half-meter drop strength of the wet pellets is ≥5 times / ball, and the bursting temperature of the wet pellets is less than 500°C.

[0020] The above drying process is as follows: the wet pellets are dried at 105-300°C for 0.5-2h to obtain dry pellets.

[0021] Furthermore, the half-meter drop strength of the dry pellets is ≥ 10 times / ball.

[0022] The above oxidation roasting process is as follows: the dry pellets are roasted at 900-1200°C for 0.5-2h, and then cooled to room temperature to obtain titanium concentrate oxidation pellets.

[0023] Furthermore, the compressive strength of the titanium concentrate oxide pellets is ≥500N / ball.

[0024] The beneficial effects of the present invention are as follows: the particle size of fine-grained titanium concentrate is extremely small, and since the production process thereof is obtained by flotation with a flotation agent, non-polar groups are attached to the surface. The interaction force between these non-polar groups and water molecules is relatively weak, and it is difficult to form a stable hydration film, resulting in an increase in the contact angle between water and the surface of the fine-grained titanium concentrate, that is, the wetting angle is greater than 90 degrees, and it is difficult for water molecules to spread on the surface of the titanium concentrate particles, and the particles are hydrophobic, so the sphericity of the fine-grained titanium concentrate is deteriorated.

[0025] The titanium-containing composite binder designed in the present invention has fine particles of raw materials for its preparation and large specific surface area, so the surface energy is increased, the chemical activity is relatively large, and it is easy to adsorb water molecules. Therefore, the contact angle with water is usually small, that is, the wetting angle is less than 90 degrees, and water molecules are more likely to spread on the surface of the particles, showing good wetting and surface adsorption properties.

[0026] The pelletizing process of fine-grained titanium concentrate with a titanium-containing composite binder of the present invention uses fine-grained titanium concentrate as a main pelletizing raw material. The added titanium-containing composite binder has good bonding performance, reduces the technical difficulty of fine-grained titanium concentrate pelletizing, and does not reduce the grade of titanium dioxide in the obtained pellets. The fine-grained titanium concentrate oxidized pellets prepared by the present invention have higher high-temperature strength and better high-temperature thermal stability, thus achieving effective utilization of fine-grained titanium concentrate resources and efficient and green recycling of titanium resources in vanadium-titanium magnetite. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a flow chart of the process for making pellets by adding a titanium-containing composite binder to fine-grained titanium concentrate. DETAILED DESCRIPTION

[0028] The technical solution of the present invention can be specifically implemented in the following manner.

[0029] 1. Types of raw materials

[0030] (1) Titanium-containing composite binder: a mixture of at least one of titanium dioxide, titanium ash powder, and titanium yellow powder and titanium slag ash in any proportion. The chemical compositions of titanium slag ash, titanium dioxide, titanium ash powder, and titanium yellow powder used in the following examples and comparative examples are shown in Table 1; the particle sizes of the titanium slag ash, titanium dioxide, titanium ash powder, and titanium yellow powder raw materials are all less than 38 μm, and their particle size distribution is shown in Table 2.

[0031] Table 1 Chemical composition of titanium-containing composite binder / wt.%

[0032] Titanium dioxide Titanium gray powder Titanium yellow powder Titanium slag ash A Titanium slag ash B <![CDATA[TiO2]]> 98.20 89.12 95.50 47.36 19.98 FeO / 1.16 / 23.77 10.91 <![CDATA[Fe2O3]]> 1.20 3.64 2.30 / / <![CDATA[Al2O3]]> 0.26 0.43 0.44 1.50 2.06 <![CDATA[SiO2]]> 0.34 1.59 0.49 12.17 32.34 S / / / 0.52 0.88 C / / / 0.65 0.57 MgO / / / 4.02 4.40 CaO / / / 0.24 1.79 <![CDATA[V2O5]]> / / 0.16 / / ZnO / / 0.10 / / <![CDATA[Cr2O3]]> / / 0.12 / / other ≤0.01 4.06 0.89 / /

[0033] Table 2 Particle size distribution of titanium-containing composite binder / %

[0034]

[0035]

[0036] (2) Fine-grained titanium concentrate: particle size less than 75 μm, titanium dioxide grade range of 40-52%. The specific chemical composition of the fine-grained titanium concentrate used in the following examples and comparative examples is shown in Table 3, and the particle size distribution is shown in Table 4.

[0037] Table 3 Chemical composition of fine-grained titanium concentrate / wt.%

[0038] <![CDATA[TiO2]]> FeO <![CDATA[Fe2O3]]> <![CDATA[Al2O3]]> <![CDATA[SiO2]]> MgO CaO other 48.4 38.27 4.58 1.02 1.92 3.32 0.84 1.65

[0039] Table 4 Particle size distribution of fine-grained titanium concentrate

[0040] Particle size / μm -150~+75 -75~+61 -61~+48 -48~+38 -38~+25 -25~+23 -23~+18 Proportion / % 0.00 0.21 1.29 29.01 44.21 23.77 1.51

[0041] 2. Raw material dosage: The mass ratio of fine-grained titanium-containing secondary resources to titanium-containing composite binder is 100:(5-20).

[0042] 3. Process flow (such as Figure 1 shown):

[0043] (1) Mixing: fully mixing the fine-grained titanium concentrate and the titanium-containing composite binder in a determined ratio;

[0044] (2) Balling: Balling is carried out by a rolling balling process, the disc balling machine rotates at a speed of 60 to 70 rpm, water is sprayed, materials are added, and balls are formed; the amount of water added is 10 to 30% of the mixed material, the wet ball particle size is 3 to 8 mm, and the wet ball half-meter drop strength is ≥ 5 times / ball;

[0045] (3) Drying: 105-300℃ drying for 0.5-2h; half-meter drop strength ≥ 10 times / ball;

[0046] (4) Oxidative roasting: roast the pellets obtained in step (3) at 900-1200° C. for 0.5-2 h in an oxidizing atmosphere, and then cool to room temperature to obtain oxidized pellets of titanium concentrate having a compressive strength of ≥500 N / ball.

[0047] The technical solution and effects of the present invention are further illustrated below through practical examples.

[0048] Example

[0049] The fine-grained titanium concentrate pelletizing process specifically includes the following steps:

[0050] (1) Ingredients: The specific ingredients of the raw materials are shown in Tables 1 and 3, the particle size distribution is shown in Tables 2 and 4, and the PVA binder is commercially available; the specific raw material ratio is as follows.

[0051] Example 1: The raw materials are fine-grained titanium concentrate and titanium-containing composite binder in a mass percentage of 100:20, and the titanium-containing composite binder is composed of titanium dioxide and titanium slag ash B in a mass ratio of 2:3; this example uses a total of 240g of raw materials, including 200g of fine-grained titanium concentrate and 40g of titanium-containing composite binder (16g of titanium dioxide and 24g of titanium slag ash B).

[0052] Example 2: The raw materials are fine-grained titanium concentrate and titanium-containing composite binder in a mass percentage of 100:14, and the titanium-containing composite binder is composed of titanium ash powder and titanium slag ash A in a mass ratio of 1:9; this example uses a total of 228g of raw materials, including 200g of fine-grained titanium concentrate and 28g of titanium-containing composite binder (2.8g of titanium ash powder and 25.2g of titanium slag ash A).

[0053] Example 3: The raw materials are fine-grained titanium concentrate and titanium-containing composite binder in a mass percentage of 100:17, and the titanium-containing composite binder is composed of titanium yellow powder and titanium slag ash B in a mass ratio of 9:11; this example uses a total of 234g of raw materials, including 200g of fine-grained titanium concentrate and 34g of titanium-containing composite binder (15.3g of titanium yellow powder and 18.7g of titanium slag ash B).

[0054] Example 4: The raw materials are fine-grained titanium concentrate and titanium-containing composite binder in a mass percentage of 100:10, and the titanium-containing composite binder is composed of titanium dioxide, titanium ash powder, titanium yellow powder and titanium slag ash B in a mass ratio of 1:2:1:4; this example uses a total of 210g of raw materials, including 200g of fine-grained titanium concentrate and 20g of titanium-containing composite binder (2.5g of titanium dioxide, 5g of titanium ash powder, 2.5g of titanium yellow powder, and 10g of titanium slag ash B).

[0055] Comparative Example 1: The raw materials are fine-grained titanium concentrate and PVA binder in a mass percentage of 100:1.5, and the concentration of the PVA binder is 0.1 g / ml; 200 g of fine-grained titanium concentrate and 30 ml of PVA binder are used in this comparative example.

[0056] Comparative Example 2: The raw materials are fine-grained iron concentrate and titanium-containing binder in a mass percentage of 100:35, and the titanium-containing binder is composed of titanium slag ash A. This embodiment uses a total of 270g of raw materials, including 200g of fine-grained titanium concentrate and 70g of titanium slag ash A.

[0057] Comparative Example 3: The raw materials are fine-grained iron concentrate and titanium-containing composite binder in a mass percentage of 100:4, and the titanium-containing composite binder is composed of titanium dioxide, titanium ash powder, titanium yellow powder and titanium slag ash B in a mass ratio of 1:2:1:4; this embodiment uses a total of 208g of raw materials, including 200g of fine-grained titanium concentrate and 8g of titanium-containing composite binder (1g of titanium dioxide, 2g of titanium ash powder, 1g of titanium yellow powder, 4g of titanium slag ash B).

[0058] Comparative Example 4: The raw materials are fine-grained iron concentrate and a titanium-containing composite binder in a mass percentage of 100:21, and the titanium-containing composite binder is composed of titanium dioxide, titanium ash powder, titanium yellow powder and titanium slag ash B in a mass ratio of 1:3:1:7; this embodiment uses a total of 242g of raw materials, including 200g of fine-grained titanium concentrate and 42g of composite binder (3.5g of titanium dioxide, 10.5g of titanium ash powder, 3.5g of titanium yellow powder, and 24.5g of titanium slag ash B).

[0059] (2) Ball making and drying:

[0060] Examples 1-4, Comparative Examples 2-4: After weighing the above raw materials and mixing them thoroughly according to the set ratio, 2 / 3 of the mixture is separated and placed in a disc granulator, the speed of the pelletizer is adjusted to 70 rpm, and it is sprayed with mist. After two minutes, small pellets appear, and the remaining mixture is slowly sprinkled into the pelletizer, and then the edge area of ​​the material is slowly sprayed with streamlined water mist. The total amount of water sprayed is shown in Table 5. After the wet pellets are formed, they are rolled for another 5 minutes, and wet pellets with a particle size range of 3-8 mm are taken out. The wet pellets are then dried, and the drying process is shown in Table 5.

[0061] Comparative Example 1: Adjust the speed of the disc granulator to 50-60r / min, take about 1 / 3 of the fine-grained titanium concentrate and put it into the bottom of the disc, and start the pelletizer. After the rolling state of the material inside the disc becomes stable, spray the mist PVA binder on the surface of the material. After about 2 minutes, slowly sprinkle the remaining fine-grained titanium concentrate into the disc pelletizer, and continue to roll so that the wet balls and powder continue to bond and grow. Adjust the nozzle so that the sprayed PVA binder is streamlined, and roll for another 3-5 minutes after the new pellets are formed. Spread the prepared wet pellets flat on an enamel tray and dry them. The drying process is shown in Table 5.

[0062] Table 5 Ball making and drying process

[0063]

[0064]

[0065] (3) Oxidation roasting: The obtained dry pellets were placed in a corundum crucible and placed in a high-temperature muffle furnace for oxidation roasting. The roasting process is shown in Table 6. The pellets were heated with the furnace. After the roasting, the pellets were taken out and allowed to cool naturally to room temperature in the air to obtain oxidized pellets.

[0066] Table 6 Oxidation roasting process

[0067]

[0068] (4) The prepared wet pellets, dry pellets and oxidized pellets were tested, and the test results are shown in Table 7.

[0069] Table 7 Pellet performance index test results

[0070]

Claims

1. A pelletizing process using fine-grained titanium concentrate and titanium-containing composite binder, characterized in that: The fine-grained titanium concentrate and the titanium-containing composite binder are mixed at a mass ratio of 100:(5-20) to obtain a mixed material, and then the titanium concentrate oxidation pellets are obtained through the processes of rolling ball forming, drying, and oxidation roasting.

2. The pelletizing process of fine-grained titanium concentrate with titanium-containing composite binder according to claim 1 is characterized in that: The particle size of fine-grained titanium concentrate is less than 75 μm, and the titanium dioxide grade is 40-52%.

3. The pelletizing process of fine-grained titanium concentrate with titanium-containing composite binder according to claim 2 is characterized in that: The particle size of the titanium-containing composite binder is less than 38 μm, and the grade of titanium dioxide is not lower than that of fine-grained titanium concentrate.

4. The pelletizing process of fine-grained titanium concentrate with titanium-containing composite binder according to claim 3 is characterized in that: The titanium-containing composite binder is a mixture of at least one of titanium dioxide, titanium ash powder, and titanium yellow powder and titanium slag ash in any proportion; Among them, the content of titanium dioxide in titanium slag ash is 20-50%, the content of titanium dioxide in titanium dioxide is ≥98%, the content of titanium dioxide in titanium ash powder is ≥89%, and the content of titanium dioxide in titanium yellow powder is ≥95%.

5. The pelletizing process of fine-grained titanium concentrate with titanium-containing composite binder according to claim 1 is characterized in that: The rolling ball making process is as follows: adding 10-30% of water by weight to the mixed material, rolling it into balls in a disc ball making machine at a rotation speed of 60-70 rpm to obtain wet pellets.

6. The pelletizing process of fine-grained titanium concentrate with titanium-containing composite binder according to claim 5 is characterized in that: The particle size of the wet pellets is 3 to 8 mm, the half-meter drop strength of the wet pellets is ≥ 5 times / ball, and the bursting temperature of the wet pellets is less than 500°C.

7. The pelletizing process of fine-grained titanium concentrate with titanium-containing composite binder according to claim 1 is characterized in that: The drying process is as follows: the wet pellets are dried at 105-300°C for 0.5-2h to obtain dry pellets.

8. The pelletizing process of fine-grained titanium concentrate with titanium-containing composite binder according to claim 7 is characterized in that: The half-meter drop strength of dry balls is ≥10 times / ball.

9. The process for pelletizing fine-grained titanium concentrate with titanium-containing composite binder according to claim 1, characterized in that: The oxidation roasting process is as follows: the dry pellets are roasted at 900-1200°C for 0.5-2h, and then cooled to room temperature to obtain titanium concentrate oxidation pellets.

10. The pelletizing process of fine-grained titanium concentrate with titanium-containing composite binder according to claim 9, characterized in that: The compressive strength of titanium concentrate oxide pellets is ≥500N / ball.

Citation Information

Patent Citations

  • Pellet binder and preparation method thereof

    CN101921911A

  • Method for granulating fine-particle titanium concentrate or titanium-rich material

    CN113215396A

  • Superfine iron ore concentrate pellets and preparation method thereof

    CN117845048A